Using spatial multi-criteria analysis as an appraisal tool for bus rapid transit trunk and feeder routes: a case study in the City of Tshwane, South Africa - Chitate, Nyasha (Department of Civil Engineering, 2019)
Private car use around the world has grown increasingly over the last decades. One effect of this is traffic congestion, which results in various detrimental environmental, economic and social impacts. Public transport has been identified as an effective solution to congestion. In South Africa, investment into public transport has led to the implementation of full and partial Bus Rapid Transit (BRT) systems. The policy and implementation measures of these BRT systems have been modelled, to varying degrees, according to Colombia’s TransMilenio BRT. However, BRT systems in South Africa have not been as successful as TransMilenio. Failures of South African BRTs can be traced back to many reasons, one of which is an inadequate conduction of an ex ante appraisal. This dissertation intended to close a literature gap on the use of ex ante appraisal in South African transport projects. At the time of composing this thesis (February 2017), South Africa did not have a standard appraisal tool for the selection of appropriate transport projects and road-based public transport routes. This resulted in systems that were not designed in context and, hence, underperformed for the context in which they were implemented. The contextually insensitive design of BRTs and the effects thereof constituted the conceptual departure point for this research. Accordingly, this dissertation aimed to explore Spatial MultiCriteria Analysis (SMCA) as a viable appraisal tool for BRT routes. The City of Tshwane formed the study area of the investigation. SMCA is a decision-support tool that combines multi-criteria analysis (MCA) and geographic information systems for evaluating decision problems whose criteria and alternatives have spatially explicit dimensions. This method was chosen over traditional appraisal tools such as MCA and cost-benefit analysis as it is more suited to routing problems. Suitable evaluation criteria were identified from five themes that were chosen from international and local trends: equity, transport efficiency and economic, social and environmental impact. Ultimately, composite suitability maps were generated according to the aforementioned themes, and optimal trunk and feeder routes were extracted by means of a vector-based network analysis. Four trunk and four feeder routes were quantitatively and qualitatively analysed. The quantitative analysis of the route involved determining the average impedance, route length and travel time of a route. The qualitative analysis involved determining if the optimal routes had changed to current or planned city routes. On average, trunk routes obtained a higher average impedance than feeder routes. All optimal routes differed to some degree from planned city routes. Following the determination of optimal routes, an uncertainty analysis showed that trunk routes were more sensitive than feeder routes. The sensitivity analysis also showed that the transport efficiency theme criteria were the most sensitive criteria, causing the highest mean average impedance change of all criteria. Transport efficiency criteria are thus the most important criteria in finding optimal routes. The method of research adopted in this study can be reproduced in any contemporary South African city with plans for BRT. Furthermore, the method of research can be improved upon by investigating standard evaluation criteria to be included in an SMCA routing problem to ensure a uniform appraisal standard.